Paranasal sinus cysts in the horse: Complications related to their presence and surgical treatment in 37 cases. (17th May 2018) - Fenner, M. F.; Verwilghen, D.; Townsend, N.; Simhofer, H.; Schwarzer, J.; Zani, D. D.; Bienert‐Zeit, A.
Summary: Background: Paranasal sinus cysts (PSC) are a common cause of equine secondary sinusitis. The outcome and associated complications have not been frequently reported. Objectives: To review the associated clinical signs, associated morbidities and outcomes of horses treated for PSC. Study design: Retrospective multicentre case series. Methods: Retrospective analysis of case records and telephone follow up survey. Results: Subjects were 37 horses 1–24 years old that were presented with nasal discharge (n = 31), facial swelling (n = 25) and epiphora (n = 19). Radiography and computed tomography allowed identification of the cyst‐induced changes including concomitant tissue destruction (n = 31), leading among other things to local nerve damage causing headshaking (n = 6) and unilateral blindness (n = 1). Radiographic changes to adjacent dental apices were present in 10 horses. Horses over 10 years old showed more of the named associated problems. Post‐operative complications included surgical site infection (SSI) (n = 11), nasofrontal suture periostitis (n = 6) and sequestration (n = 1) following removal of the PSC via osteotomy. The long‐term response to treatment was available for 28 cases with 22 horses (78.6%) fully cured, 4 (14.3%) partially cured and 2 (7.1%) not responding to treatment. In 7 horses (18.9%) there was recurrence of the cyst post‐operatively. Main limitations: Due to the study being a multicentre retrospective case series with collection of data over an extended period, there may be inconsistency in data recording and absence of reporting of some findings. Conclusions: Overall, the diagnosis and treatment of sinus cysts is relatively straightforward and carries a good prognosis. In long‐standing cases complications secondary to the expansive growth of cysts will dramatically affect the prognosis for full recovery due to pressure‐induced changes to facial bones, cheek teeth and nerves. These secondary complications mainly occurring in older horses may be due to a combination of a relatively longer period of affection and the inflexibility of older horses' bones. Cyst recurrence following treatment can occur in up to 19% of cases.